The Essence of the Concept of "Critical Thinking" And Methods of its Formation (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Critical thinking is a type of thinking – about any subject, content or problem – in which the thinker improves the quality of his or her thinking through the skillful use of the structures and intellectual standards inherent in thinking. The set of key skills required for critical thinking includes observation, the ability to interpret, analyze, draw conclusions, and make evaluations. Critical thinking applies logic and also relies on meta-knowledge and broad criteria of intelligence such as clarity, plausibility, accuracy, significance, depth, breadth and fairness. Creative imagination, value orientations and, to a lesser extent, emotionality are also components of critical thinking.